Three-dimensional conformal therapy vs. intensity modulated radiation therapy in GBM: survival, dosimetry, and side effects a systematic review and meta-analysis - Freihat, Omar; Sipos, David; Kotb, Reham; Aamir, Maria; Solymosi, Dóra; Gál, Kristóf; Mihály, Simon; Kovacs, Arpad (Frontiers in Physics, 2025)
BackgroundGlioblastoma multiforme (GBM) is an aggressive brain tumor with a poor prognosis, often managed with radiotherapy. Two primary modalities, three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy (IMRT), differ in their precision and impact on survival, side effects, and OAR sparing. However, their comparative benefits remain unclear. This meta-analysis evaluates 3D-CRT and IMRT in GBM treatment, focusing on dosimetric parameters, toxicity, and OAR sparing, with an exploratory analysis of overall survival (OS).MethodsA systematic review of 19 studies was conducted, comparing dosimetric and side effects, including planning target volume (PTV) doses (Dmean, Dmax, and Dmin), conformity and homogeneity indices, and OAR sparing.ResultsIMRT provided significant dosimetric advantages, with higher PTV Dmean (mean difference (MD) 1.26 Gy; 95% CI: 0.22–2.31; P = 0.02) and better conformity index (MD −0.21; 95% CI: −0.33 to −0.08; P = 0.001). IMRT significantly reduced doses to healthy brain (MD −1.08 Gy; 95% CI: −2.08 to −0.09; P = 0.03), brainstem (MD −0.66 Gy; 95% CI: −1.18 to −0.15; P = 0.01), optic chiasm (MD −4.93 Gy; 95% CI: −9.15 to −0.70; P = 0.02), right optic nerve (MD -5.82 Gy; 95% CI: −9.49 to −2.15; P = 0.002), and left optic nerve (MD −1.20 Gy; 95% CI: −1.77 to −0.63; P < 0.0001).ConclusionIMRT provides significant dosimetric benefits and potentially lower toxicity compared to 3D-CRT in GBM treatment. While an exploratory analysis suggests a possible OS benefit, this requires cautious interpretation due to study limitations. IMRT’s precision supports its use in GBM treatment.